Social policy review. edited by Robert Sykes, Catherine Bochel and Nick Ellison. - Sykes, Rob; Bochel, Catherine; Ellison, Nicholas, 1952- (The Policy Press, 2002)
Social Policy Review is an annual selection of commissioned articles focusing on developments and debates in social policy. Social Policy Review 14 reviews a varied and interesting selection of social policy developments in Britain and internationally, and sets current policy developments in a broader context of key trends and debates.